Rheumatic fever and rheumatic heart disease: how often we suspect infective endocarditis
Introduction: Rheumatic fever and rheumatic heart disease is a common problem in developing countries. Rheumatic valvular heart disease is one of the important risk factor for infective endocarditis. Methods: Retrospective study was conducted among 56 children admitted in cardiology ward of Kanti children hospital with the diagnosis of rheumatic fever or rheumatic heart disease during May 2008 to May 2010. Results: We found male to female ratio 2: 1, median age 12 (5-14yrs) with the most affected age group of 11-12 years. Common symptoms were fever (66%), dyspnea (68%), joint pain (50%), palpitation (30%), cough (16%) and chest pain (12%). Only 9% of patients had positive history of sore throat. Sixty percent patients were presented with features of congestive cardiac failure (CCF). A SO positive was found in 25 (44.6%) cases. The most common valvular lesion was mitral regurgitation (MR). Moderate to severe mitral regurgitation was found in 89% of cases. Tricuspid regurgitation (T R) was found in 57% of patients and aortic regurgitation (AR) in 55% of cases. Thirty-two patients (57%